2022
DOI: 10.35206/jan.1174836
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antileishmanial Activities of a Peganum Harmala and Achillea Millefolium Essential oils and their combinations against Leishmania Infantum Promastigotes

Abstract: Medicinal plants and their derivations are used as safe agents for the treatment of parasitic diseases. This preliminary study investigates antileishmanial activities of Peganum harmala essential oil (PHEO), Achillea millefolium essential oils (AMEO) and their combinations against Leishmania infantum promastigotes. A standard strain of L. infantum promastigote was cultured in a 96-well Novy-MacNeal-Nicolle media culture and antileishmanial activities of glucantime, PHEO, AMEO, an equal ratio of both and 80% PH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
0
0
Order By: Relevance
“…After this procedure, the plate was incubated in the 5 %CO2 atmosphere for 24 hours at 37 °C. At the end of this period, the plate was read in an ELISA reader, using the colorimetric technique by MTT (Ayrom, Rasouli and Shemshadi, 2021). Thus, with the IC50 and CC50 obtained, the Selectivity Index (SI) was calculated through the following equation:…”
Section: Cytotoxicity Testmentioning
confidence: 99%
“…After this procedure, the plate was incubated in the 5 %CO2 atmosphere for 24 hours at 37 °C. At the end of this period, the plate was read in an ELISA reader, using the colorimetric technique by MTT (Ayrom, Rasouli and Shemshadi, 2021). Thus, with the IC50 and CC50 obtained, the Selectivity Index (SI) was calculated through the following equation:…”
Section: Cytotoxicity Testmentioning
confidence: 99%
“…Also, the plant has anthelmintic and carminative activity (Aboutable et al, 1986;Sincich, 2002), antiviral (Soltan and Zaki, 2009), antimicrobial and anticancer (Alshuail et al, 2022;Break et al, 2022), and antifungal (Alsohaili, 2018). Additionally, studies showed its antiparasitic activity such as Trypanosoma evansi (El-Ashmawy et al, 2016), Leishmania infantum (Ayrom et al, 2021), and Blastocystis (Mokhtar et al, 2019).…”
Section: Introductionmentioning
confidence: 99%